THE ELECTROSTATIC CHARACTERISTICS OF LINEAR INSULATORS FOR CONTACT NETWORKS OF RAILWAYS - Kim, Ye. D.; Sychenko, V. H.; Kalmykov, V. L. (Science and Transport Progress, 2009)
On the base of numeric investigations on mathematical models of stationary electric field the basic electric performances of insulating suspensions from porcelain and polymeric insulators for contact nets of alternating and direct current are compared.